Infectious risk of using biomaterials for cranioplasty: polymethylmethacrylate vs. autologous bone (Research, Society and Development, 2022)
This study aimed to describe the infectious risks of using autologous bone and PMMA in cranioplasty. This is an integrative literature review of a qualitative and descriptive nature. The bibliographic survey was carried out in March and April 2022 by searching the Scientific Electronic Library Online (SciELO), Virtual Health Library (BVS), Public Medline (PubMed) and Science Direct databases and libraries. The inclusion criteria for the selection of studies were: articles published in full between the years 2013 to 2022, in English. The exclusion criteria were: monographs, dissertations, theses, Course Conclusion Papers (TCC), publications in annals of events, literature reviews and duplicate articles in one or more databases. By analyzing the articles included in this review, some authors consider that there are no significant differences regarding the infectious risk in the use of PMMA prosthesis and autologous bone, as raw material for cranioplasty. One study evaluated the impact of using antibiotics in PMMA prostheses in cranioplasty with moderate to large defects. Another study analyzed the use of prefabricated and pre-sterilized PMMA as cranioplasty material in the Indian population. One study says that prior craniotomy and PMMA cranioplasty were associated with a higher rate of postoperative infection. In another article, cranial reconstruction with autologous bone presented greater complications. The use of PMMA in cranioplasty compared to autologous bone has different outcomes in the literature.